Crop establishment and nitrogen management effects on growth, physiology and productivity of wheat under rice-wheat system - Sudarshan S; Kapila Shekhawat; S S Rathore; Rajiv K Singh; Anchal Dass; Mona Nagargade (Annals of Agricultural Research, 2022)
A field experiment was conducted during the winter season of 2020 – 21 at the ICAR–Indian Agricultural Research Institute, New Delhi to evaluate different nitrogen (N) management protocols under various crop establishment methods in wheat. The experiment was conducted in split-plot design with three replications. The treatment consisted of four crop establishment, methods viz. conventional wheat (CT-wheat), zero-tilled wheat (ZT-wheat) + rice residue @ 3t/ha, ZT-wheat without residue and stale-seed bed wheat (SSB-CT-wheat) in the main plot and 4 N management protocols viz., control (No-N), recommended N schedule (RDN), modified N schedule and leaf colour chart (LCC)-guided N scheduling in sub-plot. The growth parameters, like dry matter and indices like CGR, RGR and LAI were observed highest at 90 DAS and decreased thereafter. They remained highest in ZT+R and LCC-guided N application treatments. Various root parameters like, root length, root volume and root surface area were recorded maximum in ZT+R, followed by ZT, SSB-CT and lowest in CT. A 14.2 % increase in grain yield was recorded under ZT+R compared to CT. Also, about 15.4% increase in grain yield was recorded under LCC-guided N application-based N management compared to RDN. Also, under different establishment methods, a saving of 33.3% N under LCC-guided N application was recorded in ZT, SSB-CT and CT.